Intensidade e estrutura de medidas n\~ao tarifárias sobre as importaç\~oes brasileiras no triênio 2016-2018 - Krisley Mendes; André Araújo Luchine (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– In international literature, Brazil ranks among the most prolific countries in requesting non-tariff measures (NTMs) on their imports. When this incidence is translated into ad valorem equivalent, studies show that the costs that these measures represent place the country among the world's outliers in trade protection. This work described the incidence of NTMs that Brazil imposed its imports in the 2016-2018 at different levels of aggregation: by group of NTMs, by sector, by section of the Harmonized System (HS), by six-digit products of the HS and by partner country. The methodology is based on the inventory approach, of a descriptive and exploratory nature, with the obtainment of the frequency indicator, the coverage ratio, and the prevalence score. The results show that Brazil is more demanding in NTMs for the import of agricultural products, especially live animals, fats and oils and soybeans. In two digits of the HS, fish, meat preparations, meats and offal, coffee and fruits stand out. Among the manufactures, products from the chemical industry and vehicles stand out. In the extractive industry, more NTMs are required for bamboo and wood slabs and corrugated paper boxes.
Keywords: F13; F14; 330; Brazil; inventory approach; non-tariff measures; import